Development of a Multimodal Apparatus to Generate Biomechanically Reproducible Spinal Cord Injuries in Large Animals - Züchner, Mark; Lervik, Andreas; Kondratskaya, Elena; Bettembourg, Vanessa; Zhang, Lili; Haga, Henning A.; Boulland, Jean-Luc (Frontiers in Neurology, 2019)
Rodents are widespread animal models in spinal cord injury (SCI) research. Although they have contributed to obtaining important information, many treatments only tested in rodents have failed in clinical trials. This failure is probably a result of significant differences in the physiology, anatomy, and complexity between humans and rodents. To bridge this gap in a better way, a few research groups use pig models for SCI. Here we report the development of an apparatus to perform biomechanically reproducible SCI in large animals, including pigs. We present the iterative process of engineering, starting with a weight-drop system to ultimately produce a spring-load impactor. This device allows a graded combination of a contusion and a compression injury. We further engineered a device to entrap the spinal cord and prevent it from escaping at the moment of the impact. In addition, it provides identical resistance around the cord, thereby, optimizing the inter-animal reproducibility of the impact. We also present other tools to straighten the vertebral column and to ease the surgery. Sensors mounted on the impactor provide information to assess the inter-animal reproducibility of the impacts. Further evaluation of the injury strength using neurophysiological recordings, MRI scans, and histology shows consistency between impacts. We conclude that this apparatus provides biomechanically reproducible spinal cord injuries in pigs.